Interest of attachment use in the treatment of a large edentulous ridge: A clinical report - SAADELLAOUI , Ines; MABROUK, Yosra; MANSOUR, Lamia; TRABELSI, Mounir (International Arab Journal of Dentistry (IAJD), 2022)
The oral rehabilitation of a large edentulous ridge is complicated by mechanical and esthetic problems. The use of an axial attachment as a complementary retention device has many benefits on the prosthetic balance and the esthetically integration of the prosthesis. To manage this procedure successfully, the rigorous study of the prosthetic space and the mastering of the implementations’ steps are necessary. The purpose of this work is to present through a clinical case the various steps of the realization of a metallic framework removable partial denture with an axial attachment and to underline the contribution of this device in the case of a large edentulous ridge.